Communication as a Philosophical-Cultural Problem Notes for your Understanding - Oseda Gago, Dulio (2022)
In the 21st century, the changes caused by globalization and by the social dynamics of the new post-COVID-19 normality pose problems when it comes to defining communication relationships between individuals. From this point of view, communication problems involve several edges, difficult to face. In most cases, communication failures occur, due to the complex variety of nuances present in communication, as well as the lack of understanding of its concepts and the great breadth of cultural expressions, which can be conceived as diverse, not find space in everyday scenarios. In this sense, analyzing the scope of communication embodies a problem for philosophy, especially for philosophical anthropology, since it values communication as a representative act of cultural identity, since it responds to the ways of expressing, orally or gesturally, the human interior. This cultural universe is wide and there are not enough analyzes to define how communication influences the processes of cultural transmission. Under the hermeneutic-documentary method, the article explores the communication process, as a means to express the ontological and epistemic reality of individuals, as a meeting space, a source that enriches culture, identity and social interaction.